Evaluation of a New Culture Medium for Borrelia burgdorferi - Marques, Adriana R. (American Society for Microbiology, 2000)
We evaluated the new MPM medium for the growth of Borrelia burgdorferi. All 18 blood samples from 17 patients with Lyme disease were negative. Growth studies showed that by day 4, most organisms in MPM were not viable. Our results reinforce the use of BSK medium as the primary choice for growing B. burgdorferi.